An interactive online learning of elementary of mathematics using MOOC / Nor Aishah Md Noh … [et al.] - Md Noh, Nor Aishah; Ismail, Norul Fadhilah; Mohd Rashid, Nur Rasyida; Abdullah, Nur Lina; Muhamad Yusof, Norliza (Division of Research and Industry Linkages, 2017)
Massive Open Online Course (MOOC) is an online-based course offered worldwide where any person can freely enroll it. MOOCs Malaysia has become the Ministry Prioritization Agenda under Leap 9: Globalized Online Learning under Malaysia's' Education Development Plan 2015-2025. In line with that, UiTM is bringing this idea as another tool in its educational system to improve the effectiveness of teaching and learning process. Online learning approach has the power to attract the involvement of current generations in learning activities as student and technology are a constant companion. Consequently, we design an online course known as Elementary of Mathematics through the website openlearning.com. This course consists of five modules which covered the topic on set, system of equations and inequalities, differentiation, integration and business mathematics. The developed course is appropriate for anyone especially who are interested or experienced difficulties in studying basic and business mathematics. The open learning offers users to be more flexible concerning time, place and method of learning. Each student of the course entitles a certificate of completion once they completed all the modules and activities. We expect that this medium helps the student to develop understanding through interactive learning and acquire more fruitful learning experience in mathematics.